Health Challenges Associated with Post-Tuberculosis Sequelae Among Tuberculosis Survivors in Oyo Metropolis, Oyo State, Nigeria - Isaac Opeyemi Oguntunji; Joseph Oluwaseyi Adigun; Grace Abiodun Adesokan; Aweda Abdullahi Salaudeen; Hezekiah Adebiyi Awojobi; John Adewale Odedele; Khadijat Olubunmi Ayilara (British Journal of Multidisciplinary and Advanced Studies, 2026)
Tuberculosis (TB) is a public health problem, claiming more lives in developing countries including Nigeria. The study was purposeful to assess health challenges associated with post-TB sequelae (PTBS) among TB survivors (TBS) in Oyo metropolis, Oyo State, Nigeria. A descriptive cross-sectional survey design was adopted. The population of the study comprised all TBS in Oyo metropolis, Oyo State. A convenience sampling technique was used to select 120 respondents. Data were collected using a structured questionnaire validated by three experts. The reliability of the instrument was established using Cronbach’s alpha, yielded a coefficient of 0.82. Data were presented using mean ranking, while hypothesis was tested using Pearson correlation at the 0.05 level of significance. The findings revealed that occasional coughing (M = 3.47), anxiety due to sleeplessness caused by occasional night coughing (M = 3.47), and workplace rejection (M = 3.29) were the most physical, psychological and social health challenges affecting TBS with PTBS respectively. The result further showed that PTBS had a significant association with overall health challenges (r = .71, p < .05) of TBS. The study concluded that physical, psychological and social health statuses of TBS with PTBS were negatively affected. It was recommended that, health educators and other healthcare providers should provide appropriate health education to TBS experiencing recurrent respiratory symptoms to seek prompt care, provide community- and clinic-based mental health counselling to TBS experiencing psychological health-related problems, and educate family and community members on the importance of providing adequate care and social supports to TBS